Arrangement of Joint Commitment In Protection Of Human Rights In The Region of ASEAN - Nita, Surya (Journal of Strategic and Global Studies, 2021)
Protection of human rights must be carried out wherever humans are. The state’s obligation to fulfill, to respect, to protection is an obligation for every country, including all ASEAN countries. Human rights crimes that occurred in ASEAN countries require joint commitment arrangements between ASEAN countries to ensure the protection of human righrs in each country. So There is a need for a study to analyze the joint commitment arrangements in protecting human rights in the ASEAN region. Based on the explanation above, the study problem boundaries are formulated as follows: 1. How is the joint commitment arrangement for protection of human rights in the ASEAN region?; How are the efforts of the Indonesian government regulating the protection of human rights in the ASEAN region?. The purpose of this paper is to analyze the arrangement of joint commitments to protect human rights in the ASEAN region and to analyze the efforts to regulate the Government of Indonesia in the proctection of human rights in the ASEAN region. The method used is juridical normative with literature study and analysis used descriptive qualitative by describing human rights arrangements in the ASEAN region. Based on the explanation above, ASEAN first 1967 had a joint commitment to the Charter of Association of Southeast Asian nations and in 2012 the ASEAN Declaration of Human Rights. In 2009 the ASEAN Intergovernmental Commission on Human Rights (AICHR) was formed, which is an integral part of the ASEAN organizational structure which acts as a consultative body and provides advice on the protection of human rights. This institution is supported by the ASEAN as a joint commitment in providing protection of human rights in ASEAN countries. Second, that Indonesia has rules regarding human rights as regulated in the 1945 Constitution, Law No. 39 of 1999 about Human Rights and other regulation related to human rights. Indonesia is committed to protecting human rights both in Indonesia, in ASEAN countries and around the world. Keywords: Joint Commitment, Human Rights, ASEAN